The clinical utility of 99(m)Tc-HMPAO SPECT in Fahr's disease - GÜNAL, DİLEK; EKİNCİ, GAZANFER; DEDE, FUAT; TUROĞLU, HALİL TURGUT; İNANIR, SABAHAT; ERDİL, TANJU YUSUF; ÖNEŞ, TUNÇ (SPRINGER, 2008)
Fahr's disease is a rare neurodegenerative syndrome, characterized by massive symmetrical intracerebral calcifications of the basal ganglia, dentate nuclei of the cerebellum, and the adjacent parenchyma. Computerized tomography (CT) is considerably more sensitive to detect these intracranial calcifications than other imaging modalities. The clinical, CT scan, and 99(m)Tc-D,L-hexamethylpropylene amine oxime (99(m)Tc-HMPAO) brain perfusion single-photon emission computerized tomography (SPECT) findings in a 42-year-old woman with Fahr's disease are reported, and the clinical utility of 99(m)Tc-HMPAO SPECT findings in Fahr's disease is discussed in this article. In conclusion, 99(m)Tc-HMPAO brain perfusion SPECT seems to be useful in the clinical approach to Fahr's disease, and may provide more specific and clinically relevant information when compared with anatomical imaging.
Keywords: basal ganglia calcification; Fahr's disease; idiopathic bilateral symmetrical striopallidodentate calcinosis; SPECT; 99(m)Tc-HMPAO; BILATERAL STRIOPALLIDODENTATE CALCINOSIS; CEREBRAL-BLOOD-FLOW; BASAL GANGLIA; COMPUTED-TOMOGRAPHY; INTRACRANIAL CALCIFICATIONS; MR; CT